At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

HELP PLS ITS ALGEBRA 1


HELP PLS ITS ALGEBRA 1 class=

Sagot :

Answer:

[tex] - \frac{2}{6} [/tex]

Step-by-step explanation:

Use distributive property to simplify both sides.

[tex] \frac{1}{6} (1 - 6x) = - \frac{1}{3} ( 6x + \frac{1}{2} )[/tex]

Use the Golden Rule of Algebra: (What we do to one side, we must do to the other).

[tex] \frac{1}{6 } - x = - 2x - \frac{1}{6} [/tex]

[tex] \frac{1}{6} = - x - \frac{1}{6} [/tex]

[tex] \frac{2}{6 } = - x[/tex]

[tex]x = - \frac{2}{6} [/tex]

Answer:

Step-by-step explanation:

[tex]\frac{1}{6}[/tex](1-6x) = - [tex]\frac{1}{3}[/tex](6x+[tex]\frac{1}{2}[/tex])

distribute in the fractions

[tex]\frac{1}{6}[/tex] - 1x = -2x - [tex]\frac{1}{6}[/tex]

subtract [tex]\frac{1}{6}[/tex]  from both sides

-[tex]\frac{1}{6}[/tex]+[tex]\frac{1}{6}[/tex]-1x = -2x -[tex]\frac{1}{6}[/tex]-[tex]\frac{1}{6}[/tex]

-1x = -2x -[tex]\frac{2}{6}[/tex]

-x = -2x - [tex]\frac{1}{3}[/tex]

[tex]\frac{1}{3}[/tex] = -2x + x

[tex]\frac{1}{3}[/tex] = -x

- [tex]\frac{1}{3}[/tex] = x

x = - [tex]\frac{1}{3}[/tex]

see?  :/